Pembelajaran Berdiferensiasi Menggunakan Teknik Modelling Pada Materi Ungkapan Congratulation, Hope And Wish di SMP - Aryanti, Nurita (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2024)
This study is titled "Differentiated Instruction Using Modelling Techniques on Expressions of Congratulation, Hope, and Wish in Junior High School." The research problem addressed is, "How does the implementation of differentiated instruction using modelling techniques on expressions of congratulation, hope, and wish enhance the understanding of junior high school students?" The objective of this study is to determine the effectiveness of implementing differentiated instruction with modelling techniques in improving students' understanding of expressions of congratulation, hope, and wish in junior high school. The methodology used in this research is descriptive qualitative. The findings show that the application of differentiated instruction with modelling techniques can enhance students' understanding and skills in using expressions of congratulation, hope, and wish. The modelling techniques used include direct demonstrations by the teacher, the use of concrete examples, and repeated practice involving active student participation. Based on the analysis, differentiated instruction with modelling techniques proves effective in accommodating various learning styles and improving students' learning outcomes on this material.